Pengaruh Penggunaan Media Komik Digital Muatan Bahasa Indonesia Terhadap Minat Baca Siswa - azizah, rosiana (Sangkalemo : The Elementary School Teacher Education Journal, 2025)
This study aims to explore the impact of digital comic-based learning on the reading interest of fourth-grade students. Utilizing a quantitative method and experimental design, the researcher divided the subjects into two groups: an experimental group using digital comics and a control group using traditional learning methods. Data were collected through pre-tests and post-tests to measure changes in reading interest. The results indicate that the use of digital comics significantly enhances students' reading interest. The average pre-test score was 54.57, which increased to 74.35 after the implementation of digital comics. Statistical tests showed a p-value < 0.05, indicating a significant relationship between the independent variable (digital comic-based learning) and the dependent variable (reading interest). Discussion of the results reveals that digital comics can make the learning process more engaging and interactive, thereby increasing students' motivation and reading skills. Therefore, it is recommended to consider integrating digital comics into the Indonesian language curriculum to enhance students' reading interest and literacy